Recognition and redemption: visions of safety and justice in Black Lives Matter - Loader, I (Universidade Estadual de Londrina, 2021)
In this paper, I recover and appraise the principal ways in which movements motivated by the ideal of racial justice have sought to transform how questions of police and punishment are imagined and acted upon. The focus of the enquiry is the visions of safety and justice found in Black Lives Matter. I offer an interpretive reconstruction and appraisal of the core claims found with the Black Lives Matter movement and their ideological lineage and affinities. The paper seeks to understand those claims anthropologically, from the inside, trying to offer a best‑case rendition of their contexts and appeal. It also seeks to situate these claims politically (while recognizing diversity and avoiding the imposition of some spurious unity) with a view to grasping the normative character of the alternative plausible world that Black Lives Matter projects and seeks to usher into being. My claim is that one finds in Black Lives Matter a tension between a politics of self‑determination and a wider politics of transformative redemption. Neste artigo, recupero e avalio as principais formas pelas quais movimentos motivados pelo ideal de justiça racial têm buscado transformar o modo como policiamento e punição são imaginados e postos em prática. O foco da investigação são as visões de segurança e justiça encontradas no movimento Black Lives Matter. Proponho uma reconstrução interpretativa e uma avaliação das reivindicações centrais encontradas no movimento e sua linhagem ideológica e afinidades. Neste artigo procuro entender essas reivindicações antropologicamente, de dentro, tentando oferecer uma best‐case rendition do contextos e dos apelos formulados. Também procuro situar politicamente essas reivindicações (ao mesmo tempo em que reconheço a diversidade e evito a imposição de alguma unidade espúria) com vistas a apreender o caráter normativo do mundo alternativo plausível que o Black Lives Matter projeta e busca inaugurar. Minha afirmação é que se encontra no Black Lives Matter uma tensão entre uma política de autodeterminação e uma política mais ampla de redenção transformadora.